2014
DOI: 10.1039/c4fd00151f
|View full text |Cite
|
Sign up to set email alerts
|

Three bisphosphonate ligands improve the water solubility of quantum dots

Abstract: Synthesised Quantum Dots (QDs) require surface modification in order to improve their aqueous dispersion and biocompatibility. Here, we suggest bisphosphonate molecules as agents to modify the surface of QDs for improved water solubility and biocompatibility. QDs_TOPO (CdSe/ZnS-trioctylphosphine oxide) were synthesised following modification of the method of Bawendi et al. (J. Phys. Chem. B, 1997, 101, 9463-9475). QDs surface modification is performed using a ligand exchange reaction with structurally differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For example, Ghani et al, replaced the original hydrophobic tri-octyl phosphine oxide (TOPO) ligands on CdSe/ZnS QDs with different types of water-soluble bisphosphonate (BIP)-based ligands, such as ethylene diphosphonate (EDP), imido diphosphonate (IDP), and methylene diphosphonate (MDP). The results showed that the exchanged ligand improved the water solubility and dispersal of CdSe/ZnS QDs [ 22 ]. Furthermore, EDP-, IDP-, and MDP-conjugated CdSe/ZnS QDs were shown to have lower toxicity effects compared to CdSe/ZnS QDs conjugated with TOPO ligands.…”
Section: Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ghani et al, replaced the original hydrophobic tri-octyl phosphine oxide (TOPO) ligands on CdSe/ZnS QDs with different types of water-soluble bisphosphonate (BIP)-based ligands, such as ethylene diphosphonate (EDP), imido diphosphonate (IDP), and methylene diphosphonate (MDP). The results showed that the exchanged ligand improved the water solubility and dispersal of CdSe/ZnS QDs [ 22 ]. Furthermore, EDP-, IDP-, and MDP-conjugated CdSe/ZnS QDs were shown to have lower toxicity effects compared to CdSe/ZnS QDs conjugated with TOPO ligands.…”
Section: Ligandsmentioning
confidence: 99%
“…Furthermore, EDP-, IDP-, and MDP-conjugated CdSe/ZnS QDs were shown to have lower toxicity effects compared to CdSe/ZnS QDs conjugated with TOPO ligands. Additionally, the study found that EDP and MDP were significantly taken up by IGROV-1 ovarian cancer cells compared to IDP-conjugated CdSe/ZnS QDs [ 22 ]. The difference in the cellular uptake of QDs with different target ligands showed that certain ligands are more suitable than others for biological applications.…”
Section: Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…For bioimaging applications of quantum dots, exchange of native hydrophobic ligands with small molecules can achieve water solubility while preserving a small hydrodynamic radius. Several types of hydrophilic ligands have been identified for ligand exchange of fluorescent QDs. Numerous studies on thiol anchoring groups show their high binding strength to the QD surface. However, thiols are not an ideal solution for bioimaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the surface of QDs can be modified with different types of ligands. The choice of appropriate ligand is a crucial parameter because the ligands affect stability, dispersibility and water solubility of QDs (Abdul Ghani et al 2014). Despite the impact on the physical and chemical parameters, ligands can also influence QDs interaction with cells or living organisms (Biju et al 2010;Jin and Hildebrandt 2012;Karabanovas et al 2014).…”
Section: Introductionmentioning
confidence: 99%